Analisis Komparasi Pemikiran Ibnu Hazm dan Syafi’i terhadap Hukum Musik - Muhammad Yusram; Wijaya , Hendra; Iskandar , Azwar; Moh. Fadli (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This research aims to examine the law of music in the review of Islamic law by comparing the opinion that forbidding the music especially from Shafi’i and opinion that allowing the music especially from Ibnu Ḥazm. This research used library research methods with comparative analysis approach. The results found some important findings. First, Ibn Hazm argued that the law of all things that have no clear evidence of it is permissable, including music. There are many flaws in the hadiths and aṡar that are expressed by scholars who forbid music, including the weakness of the mustard and the use of the word in narration that raises doubts in it. Second, Shafi'i allows certain instruments under certain circumstances such as tabla instruments used during war, not for something that neglects such as singing. Shafi'i hates acts that neglect a person from the Qur'an such as listening to a song even though there is a remembrance of Allah. There is a contention or comment from the scholars to Ibn Ḥazm who doubts the validity of Bukhari as a reliable hadith. Third, the differences in scholars on this matter are specific to Ibnu Ḥazm and Shafi'i's views, not including disagreements that allow a person to choose an opinion that he believes based on the evidence he has heard from both. This is because there has been clear evidence of cancelling one of the views of both. In this case, Ibn Ḥazm's opinion of the hadith which he thought was weak turned out to be a valid hadith and agreed upon by most scholars.